RADT-35. A PROSPECTIVE REGISTRY STUDY OF 68GA-DOTATATE PET INCORPORATION INTO TREATMENT PLANNING OF INTRACRANIAL MENINGIOMAS. (14th November 2022) - Perlow, Haley; Prasad, Rahul; Siedow, Michael; Gokun, Yevgeniya; Matsui, Jennifer; Blakaj, Dukagjin; Beyer, Sasha; Thomas, Evan; Raval, Raju; Chakravarti, Arnab; Prevedello, Daniel; Hardesty, Douglas; et al.
Abstract: Introduction: The current standard for meningioma radiation planning involves MRI-based image guidance. SSTR ligands such as 68 Ga-DOTATATE are being explored for meningioma radiotherapy treatment planning due to universal expression of somatostatin receptor 1/2 in meningioma tissue. We hypothesize that 68 Ga-DOTATATE PET utilization can reduce the risk of local failure (LF) through precise radiation planning and may also suggest that patients who have local PET avidity after a perceived GTR may be poor observation candidates. METHODS: A single institution prospective registry study was created and included intracranial meningioma patients who received a 68 Ga-DOTATATE PET scan to assist with radiation oncologist decision-making. These were ordered for all meningioma patients as a departmental standard. Patients who received a PET scan from 1/1/2018-2/25/2022 were eligible for inclusion. RESULTS: 60 patients were treated in this prospective registry. 22%, 72%, and 7% were World Health Organization (WHO) high, intermediate, and low-risk, respectively. After completing their PET scan, 48, 11, and 1 patient(s) proceeded with RT, observation, or redo craniotomy. The median follow up was 16 months (IQR 8.3-23.1). 3 patients (5%) experienced LF between 9.2-28.5 months after diagnosis. 2 patients with LF had PET-avid disease in their post-operative cavity and elected for observation prior to recurrence, and 1 high-risk patient with multifocal disease experienced LF 2 years after a second radiation course and multiple previous recurrences. LF rates after radiation were 0%, 0%, and 8% in the low, intermediate, and high-risk cohorts, respectively. There were no Grade 3 or higher toxicities attributed to PET-guided radiation. CONCLUSION: This is the largest known population of intracranial meningioma patients followed by physicians who utilized 68 Ga-DOTATATE PET guided therapy. Only 1 patient experienced LF after receiving PET-guided radiation therapy, likely due to a radioresistant histology. Incorporating 68 Ga-DOTATATE PET into future trials may assist with clinician decision-making and improve patient outcomes.